Usability testing pada sistem presensi aplikasi HRM Talenta dengan menggunakan metode cognitive walkthrough - Tileng, Kartika Gianina; Lim, Alex Sander (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
Human Resource Management (HRM) is a very important part of an organization. In the digital era, HRM can be done more efficiently through mobile applications that allow access to employee data, HRM processes, or online attendance. However, the ability of an HRM mobile application to succeed depends on the usability factor or ease of use by users.  Talenta is one of Mekari's business platforms that provides a complete solution for all Human Resources (HR) and payroll management issues. Talenta is an application that will be used for Usability Testing using Cognitive Walkthrough. The initial stage in starting Usability Testing on the mobile-based Talenta application with the Cognitive Walkthrough method begins with conducting a literature study, learning the system or application, then making scenario questions based on the system. Then, respondents will be asked to complete the scenario questions. The scenario data collected includes; data on success in completing the scenario, data on errors in completing the scenario, and data on the time required to complete the scenario. Finally, the interview stage will be continued with the respondents on the scenarios that have been carried out. The scenario and interview data will be analyzed to calculate the effectiveness and efficiency aspects of the Talenta application. After the analysis stage, users will be given a System Usability Scale (SUS) questionnaire to be answered using Google Form using a Likert scale. The results of the questionnaire will be analyzed using SUS calculations, and then suggestions and conclusions will be given in the aspect of user learning ability. After usability testing of Talenta mobile application using Cognitive Walkthrough and SUS methods, the following results were obtained: 78% effectiveness; 0.10 seconds efficiency; and 67 learning ability level. Talenta has met the usability criteria for mobile applications in general, including effectiveness and efficiency in using the ISO 9241-11 model. However, there are still shortcomings in the user learnability level. To improve the usability of this application, it is recommended to change the layout, menu, add features, as well as clarify some display features.